Methodology for Designing and Creating Rubrics to Assess Competencies - Aguayo-Hernández, Claudia H.; Pineda Garín, María Jose; Huereca Alonzo, Soraya; Vázquez-Villegas, Patricia (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
A methodology for designing holistic rubrics to assess competencies in a Mexican university (Tec21) is presented. It ensures standardized and reliable evaluations, emphasizing collaboration and adaptability in other contexts. The rubrics focus on key behaviors, enabling a comprehensive assessment of student performance. A glossary supports consistent interpretation and effective implementation after faculty training. The holistic and task-specific rubrics offer flexibility and promote fair, meaningful assessment practices.